A super lubricating composite coating for aviation engine oil and preparation method thereof

By combining surface modification of inorganic particles and mixed emulsions, a composite coating that achieves superlubrication in an aircraft engine oil lubrication environment was prepared, which solved the problem that the prior art could not achieve superlubrication in extreme environments, significantly reduced friction and wear, and improved the reliability and life of parts.

CN119144226BActive Publication Date: 2025-03-11NORTHWESTERN POLYTECHNICAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411600986.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-11
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art cannot achieve superlubrication in aero engine oil lubrication environment, especially in extreme environmental conditions such as low speed and heavy load, which is difficult to meet the requirements of lower energy consumption, higher reliability and longer life of the new generation of key aerospace components.

Method used

A superlubricated composite coating preparation method for aircraft engine oil is adopted, including surface modification of inorganic particles, mixing perfluoroethylene propylene copolymer emulsion, polytetrafluoroethylene emulsion and polyethersulfone emulsion to form a blended dispersion liquid, and coating and curing under lubricating conditions of aircraft engine oil to achieve the self-layering effect of composite coating.

Benefits of technology

It achieves a stable superlubrication effect under aircraft engine oil lubrication, reduces friction and wear, improves the reliability and life of the aeromechanical transmission system, and supports the independent research and development of key components of aircraft engines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144226B_ABST
    Figure CN119144226B_ABST
Patent Text Reader

Abstract

The present application relates to a super-lubricating composite coating. In view of the current lack of super-lubricating materials and design methods for aviation engine lubricating oil environments, a super-lubricating composite coating for aviation engine oil and a preparation method thereof are provided. The inorganic particles are first surface-modified to improve the interfacial compatibility and wear resistance of the composite coating. The polyethersulfone emulsion is used as a binder to improve the bonding force between the composite coating and the substrate. The perfluoroethylene propylene copolymer emulsion and polytetrafluoroethylene can provide a lubricating phase to achieve a super-lubricating lubricating surface, and also have high chemical stability. The sequence of steps in the preparation method of the super-lubricating composite coating of the present application is conducive to the dispersion of the perfluoroethylene propylene copolymer emulsion and polytetrafluoroethylene, so that a uniformly dispersed and non-precipitated blended solution can be obtained. In addition, the super-lubricating composite coating of the present application can achieve self-stratification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a super-lubricating composite coating, and specifically to a super-lubricating composite coating for aviation engine oil and a preparation method thereof. Background Art

[0002] With the rapid development of industry and cutting-edge technology, high-end manufacturing such as aviation and aerospace is also moving towards "faster" and "safer". Traditional lubricating materials and technologies can no longer meet the requirements of lower energy consumption, higher reliability and longer life of the new generation of key aerospace components, especially in extreme environmental conditions such as low speed and heavy load. Key aviation components such as bearings, gears, and seals are facing failures due to friction and wear. Based on the above situation, superlubricating materials and technologies are considered to be an effective way to solve friction and wear, especially to help achieve independent development of long-life and high-reliability aircraft engines.

[0003] At present, superlubrication based on water-based lubricants has been widely reported, but there are no public reports on superlubrication under aviation engine oil lubrication conditions. Related research still faces great challenges and is basically blank. Ester lubricants represented by pentaerythritol esters are the mainstream lubricants currently used in aviation engines. Aviation engine oil is difficult to replace because of compatibility issues with materials such as rubber seals / gears / bearings. However, there are currently no public reports on coatings and technologies that can achieve superlubricity under aviation engine oil lubrication. Therefore, there is an urgent need to develop superlubricity materials and design methods for aviation engine lubricating oil environments. Summary of the invention

[0004] This application aims to solve the technical problem of the current lack of super-lubricating materials and design methods for aviation engine lubricating oil environments, and provides a super-lubricating composite coating for aviation engine oil and a preparation method thereof.

[0005] In order to achieve the above objectives, this application adopts the following technical solutions:

[0006] In the first aspect, the present application proposes a method for preparing a super-lubricating composite coating for aviation engine oil, comprising:

[0007] S1, performing surface modification treatment on the inorganic particles to make the surface of the inorganic particles wettable, washing and heat-drying for 1-3 hours to obtain modified inorganic particles;

[0008] S2, mixing a perfluoroethylene propylene copolymer emulsion, a polytetrafluoroethylene emulsion, and a polyethersulfone emulsion to obtain a mixed emulsion;

[0009] S3, mixing the modified inorganic particles with the mixed emulsion, adding a solvent, and obtaining a blended dispersion;

[0010] S4, coating the blended dispersion on the surface of a workpiece lubricated with aviation engine oil, drying it, and then heating and curing it at a temperature of 280-380° C. for 100-300 min to obtain a composite coating.

[0011] Furthermore, in step S1, the surface modification of the inorganic particles comprises:

[0012] Dopamine or a silane coupling agent is used to perform surface modification treatment on any one of carbon fiber, graphene, and titanium dioxide nanoparticles.

[0013] Furthermore, in step S1, the surface modification of the inorganic particles comprises:

[0014] Dopamine is used to perform surface modification on carbon fibers, wherein the average length of the carbon fibers is 1 um to 3 um.

[0015] Furthermore, in step S1, the surface modification of the inorganic particles comprises:

[0016] Dopamine is used to perform surface modification on titanium dioxide nanoparticles, wherein the average particle size of the titanium dioxide nanoparticles is 100 nm to 200 nm.

[0017] Furthermore, in step S2, the average particle size of the polytetrafluoroethylene emulsion and the polyethersulfone emulsion is 100 nm to 300 nm.

[0018] Further, in step S3, the modified inorganic particles are mixed with the mixed emulsion, comprising:

[0019] The modified inorganic particles are 1 to 3 parts, the perfluoroethylene propylene copolymer emulsion is 10 to 20 parts, the polytetrafluoroethylene is 10 to 20 parts, and the polyether sulfone is 60 to 80 parts.

[0020] Furthermore, in step S3, the solvent includes one or more of water, alkylamine, polyethyleneimine, polyacrylic acid, and polyethylene glycol.

[0021] Further, in step S4, the heating and curing comprises:

[0022] Heat cure at 280-300°C for 100-150 min.

[0023] In a second aspect, the present application proposes a super-lubricating composite coating for aviation engine oil, which is obtained by using the above-mentioned method for preparing the super-lubricating composite coating for aviation engine oil.

[0024] Compared with the prior art, this application has the following beneficial effects:

[0025] The present application proposes a method for preparing a super-lubricating composite coating for aviation engine oil, firstly, the inorganic particles are surface modified to improve the interfacial compatibility and wear resistance of the composite coating, and the polyethersulfone emulsion is used as a binder to improve the bonding force between the composite coating and the substrate, and the perfluoroethylene propylene copolymer emulsion and polytetrafluoroethylene can provide a lubricating phase to achieve a super-lubricating lubricating surface, and also have high chemical stability. Although there is no chemical reaction between the components, a comprehensive effect is achieved through compounding. Furthermore, the sequence of steps of the method for preparing a super-lubricating composite coating of the present application is conducive to the dispersion of the perfluoroethylene propylene copolymer emulsion and polytetrafluoroethylene, so that a uniformly dispersed and non-precipitated blend solution can be obtained. More importantly, the super-lubricating composite coating of the present application can achieve self-stratification. During the curing process, polytetrafluoroethylene and polyethersulfone emulsions are cured first, and the perfluoroethylene propylene copolymer emulsion will form a nucleus on the surface of polytetrafluoroethylene and polyethersulfone, thereby growing on the surface to achieve self-stratification. On the one hand, self-stratification can ensure the high bonding force between the composite coating and the substrate and ensure the long-term effectiveness of the coating. On the other hand, a high fluoride content can be obtained on the surface of the composite coating by stratification, thereby greatly reducing the adhesive friction resistance and achieving super lubrication under the lubricating oil of the aircraft engine. The composite coating obtained by the preparation method of this application is not only highly stable and suitable for large-scale rapid preparation, but also can achieve long-life stable macroscopic super lubrication behavior under the lubrication of the aircraft engine lubricating oil, which is expected to significantly reduce the friction and wear of the aviation mechanical transmission system and help the independent research and development of key components of the aircraft engine.

[0026] The present application also proposes a super-lubricating composite coating for aviation engine oil, which is obtained by adopting the above-mentioned method for preparing the super-lubricating composite coating for aviation engine oil and has all the above-mentioned advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0028] Figure 1 This is a SEM image of the modified inorganic particles in Example 1 of the present application;

[0029] Figure 2 This is a SEM image of the surface of the self-stratified composite coating in Example 1 of the present application;

[0030] Figure 3 This is a SEM image of the cross section of the self-stratified composite coating in Example 1 of the present application;

[0031] Figure 4 This is a schematic diagram of the friction test results of the composite coating obtained in Example 1 of the present application;

[0032] Figure 5 This is a schematic diagram of the friction test results of the composite coating obtained in Example 3 of the present application;

[0033] Figure 6 This is a schematic diagram of the friction test results of the composite coating obtained in Comparative Example 1 of the present application;

[0034] Figure 7 This is a SEM image of the cross section of the non-self-stratifying composite coating obtained in Comparative Example 1 of the present application;

[0035] Figure 8 This is a schematic diagram of the friction test results of the composite coating obtained in Comparative Example 2 of the present application;

[0036] Fig. 9 This is a schematic diagram of the composite coating friction test results obtained in Comparative Example 3 of the present application;

[0037] Fig.10 This is a schematic diagram of the composite coating friction test results obtained in Comparative Example 4 of the present application. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0039] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0040] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0041] In the description of the embodiments of the present application, it should be noted that if the terms "upper", "lower", "horizontal", "inner", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the drawings, or the orientation or position relationship in which the invented product is usually placed when used. It is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0042] In addition, if the term "horizontal" appears, it does not mean that the component must be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", which does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0043] In the description of the embodiments of the present application, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0044] Ester lubricants perform well in high-temperature environments and can meet the high-temperature operation requirements of aircraft engines. They help reduce wear on internal engine components and extend engine life. Compared with traditional mineral oils, ester lubricants are more biodegradable and environmentally friendly. Therefore, ester lubricants are the mainstream lubricants used in current aircraft engines and are difficult to replace.

[0045] In the fields of aviation and aerospace, the requirements for lubrication are gradually increasing, among which superlubricating materials and technologies are considered to be an effective way to solve friction and wear.

[0046] In recent years, superlubricating materials and related technologies have received extensive attention from researchers. For example, in the Chinese invention patent application with publication number CN118185459A, a solid-liquid composite superlubricating coating based on self-assembled monolayer and its preparation method are disclosed, wherein a hydroxylated workpiece is immersed in an alkyltrichlorosilane reaction reagent, and a self-assembled monolayer is obtained on the surface of the workpiece after reaction and curing; a liquid lubricating medium is applied to the surface of the workpiece with the self-assembled monolayer to prepare a solid-liquid composite coating that realizes superlubricating behavior of sliding parts during a short running-in period. Another example is in the Chinese invention patent application with publication number CN118028042A, a lubricant composition containing ionic liquid and a method for achieving superlubricity are disclosed, wherein a polyhydroxy hydrogen bond donor ionic liquid is used as a base lubricating liquid, and carbon quantum dots are used as competitive ligands. The carbon quantum dots can effectively regulate the width / span of the cluster size distribution in the lubricating liquid, greatly reduce the friction coefficient during relative motion of the friction pair, and achieve superlubricity after the friction pair undergoes a short running-in process.

[0047] However, there is still a lack of coatings and technologies that achieve super lubricity in the lubrication environment of aviation engine oil. Based on the above situation, this application proposes a super lubricity composite coating for aviation engine oil and a preparation method thereof, which is described in detail below in conjunction with embodiments and drawings.

[0048] Embodiment 1:

[0049] A method for preparing a super-lubricating composite coating for aviation engine oil, oriented to 5750 aviation lubricating oil, may include:

[0050] S1, surface modification of inorganic filler.

[0051] The carbon fiber as inorganic particles was dried, mixed with dopamine and added into deionized water, stirred and heated at 100°C, filtered, and dried in a vacuum drying oven at 100°C for 2 hours to obtain modified carbon fiber. The amount of dopamine added was 3% of the mass of the carbon fiber, and the average length of the carbon fiber was 1 um. Figure 1 The following is a SEM (Scanning Electron Microscope) image of the modified carbon fiber after drying. Figure 1 The particle size distribution of the modified carbon fiber after drying can be seen in the figure.

[0052] It should be noted that the inorganic particles may also be inorganic fillers with high hardness and high toughness, such as graphene or titanium dioxide nanoparticles. In other embodiments of the present application, a silane coupling agent may also be used instead of dopamine.

[0053] S2, preparation of mixed emulsion.

[0054] Take 0.1g polytetrafluoroethylene emulsion, 0.1g perfluoroethylene propylene copolymer emulsion, and 0.6g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 12.5 wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 12.5 wt%, and the weight percentage of polyethersulfone emulsion is 75 wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 150 nm. S3, preparation of blended dispersion.

[0055] Take 0.3g of modified carbon fiber, 0.3g of mixed emulsion and 1.0g of deionized water respectively and add them into the reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0056] S4, substrate (workpiece surface lubricated by aviation engine oil) pretreatment.

[0057] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0058] In practical applications, the material of the substrate can be titanium alloy, multi-principal alloy, etc., and this application does not impose any specific limitation.

[0059] S5, preparation of composite coating.

[0060] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven at 60°C for drying. After drying, it is placed in a muffle furnace and further sintered and cured at 280°C for 150 minutes to obtain a workpiece coated with a composite coating.

[0061] In practical applications, the blended dispersion liquid can be coated with fluorine by drip coating, spray coating or spin coating, etc., and this application does not make any specific restrictions.

[0062] In order to verify the effect of the composite coating technology in Example 1, a friction test experiment was conducted. The workpiece coated with the composite coating was placed on a multifunctional friction and wear tester for friction testing, and 0.2g of 5750 lubricating oil was added to the friction position, while a load of 5 N and a linear speed of 18 mm / s were applied. Figure 4 The figure shows the friction test results of the composite coating obtained in Example 1. Figure 4In the figure, the vertical axis Coefficient of Friction (COF) is used to describe the friction between two contacting surfaces. Figure 4 It can be seen that the composite coating obtained in Example 1 can obtain a stable superlubricity state, COF=0.005.

[0063] In addition, if Figure 2 As shown, it is a SEM image of the surface of the superlubricating composite coating obtained in the embodiment, Figure 3 : is a SEM image of the cross section of the self-stratified composite coating in Example 1 of the present invention. Figure 2 and Figure 3 It can be seen that the surface of the superlubricating composite coating is relatively smooth, self-stratification occurs in the middle of the coating, and fluoride is located in the upper middle part of the coating.

[0064] Embodiment 2:

[0065] A method for preparing a super-lubricating composite coating for aviation engine oil, which is oriented to 5750 aviation lubricating oil, may include:

[0066] S1, surface modification of inorganic filler.

[0067] The graphene particles were dried, mixed with a silane coupling agent, added to deionized water, stirred and heated at 100° C., filtered, and dried in a vacuum drying oven at 100° C. for 2 hours to obtain modified graphene particles. The amount of the silane coupling agent added was 3% of the mass of the graphene particles.

[0068] S2, preparation of mixed emulsion.

[0069] Take 0.2g polytetrafluoroethylene emulsion, 0.2g perfluoroethylene propylene copolymer emulsion, and 0.6g polyethersulfone emulsion respectively, add them to the reagent bottle, shake them preliminarily, and then use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 40rpm, and the ultrasonic time is 20min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 20wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 20wt%, and the weight percentage of polyethersulfone emulsion is 60wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 150nm.

[0070] S3, preparation of blended dispersion.

[0071] Take 0.3g of modified graphene particles, 0.3g of mixed emulsion, and 1.0g of deionized water respectively, mix and add them into a reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0072] S4, substrate pretreatment.

[0073] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0074] S5, preparation of composite coating.

[0075] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven at 60°C for drying. After drying, it is placed in a muffle furnace and further sintered and cured at 280°C for 150 minutes to obtain a workpiece coated with a composite coating.

[0076] Embodiment 3:

[0077] A method for preparing a super-lubricating composite coating for aviation engine oil, oriented to NP451 aviation lubricating oil, may include:

[0078] S1, surface modification of inorganic filler.

[0079] The titanium dioxide nanoparticles were dried, mixed with a silane coupling agent, added to deionized water, stirred and heated at 100°C, filtered, and dried in a vacuum drying oven at 100°C for 2 hours to obtain modified titanium dioxide nanoparticles. The amount of the silane coupling agent added was 3% of the mass of the titanium dioxide nanoparticles, and the average particle size of the titanium dioxide nanoparticles was 100 nm.

[0080] S2, preparation of mixed emulsion.

[0081] Take 0.1g polytetrafluoroethylene emulsion, 0.1g perfluoroethylene propylene copolymer emulsion, and 0.6g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 12.5wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 12.5wt%, and the weight percentage of polyethersulfone emulsion is 75wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 100 nm.

[0082] S3, preparation of blended dispersion.

[0083] Take 0.3g of modified titanium dioxide nanoparticles, 0.3g of mixed emulsion, and 1.0g of polyethyleneimine respectively and add them into a reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0084] S4, substrate pretreatment.

[0085] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0086] S5, preparation of composite coating.

[0087] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven for drying at 60°C. After drying, it is placed in a muffle furnace and further sintered and cured at 300°C for 100 minutes to obtain a workpiece coated with a composite coating.

[0088] In order to verify the effect of the composite coating technology in Example 3, a friction test experiment was conducted. The workpiece coated with the composite coating was placed on a multifunctional friction and wear tester for friction testing, and 0.2g of NP451 aviation lubricant was added to the friction position, while a load of 5 N and a linear speed of 18 mm / s were applied. Figure 5 The figure shows the friction test results of the composite coating obtained in Example 3. Figure 5 In the figure, the vertical axis Coefficient of Friction (COF) is used to describe the friction between two contacting surfaces. Figure 5 It can be seen that the composite coating obtained in Example 3 can obtain a stable superlubricity state, COF=0.008.

[0089] Embodiment 4:

[0090] A method for preparing a super-lubricating composite coating for aviation engine oil, oriented to NP451 aviation lubricating oil, may include:

[0091] S1, surface modification of inorganic filler.

[0092] The titanium dioxide nanoparticles were dried, mixed with dopamine, added to deionized water, stirred and heated at 100°C, filtered, and dried in a vacuum drying oven at 100°C for 2 hours to obtain modified titanium dioxide nanoparticles. The amount of dopamine added was 3% of the mass of the titanium dioxide nanoparticles, and the average particle size of the titanium dioxide nanoparticles was 200 nm.

[0093] S2, preparation of mixed emulsion.

[0094] Take 0.15g polytetrafluoroethylene emulsion, 0.15g perfluoroethylene propylene copolymer emulsion, and 0.7g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 15wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 15wt%, and the weight percentage of polyethersulfone emulsion is 70wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 300 nm.

[0095] S3, preparation of blended dispersion.

[0096] Take 6g of modified titanium dioxide nanoparticles, 6g of mixed emulsion, and 1.0g of polyethylene glycol respectively and add them to the reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0097] S4, substrate pretreatment.

[0098] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0099] S5, preparation of composite coating.

[0100] The blended dispersion was coated on the clean surface of the workpiece and placed in a vacuum drying oven for drying at 60° C. After drying, it was placed in a muffle furnace and further sintered and cured at 380° C. The sintering and curing time was 100 min to obtain a workpiece coated with a composite coating.

[0101] Embodiment 5:

[0102] A method for preparing a super-lubricating composite coating for aviation engine oil, oriented to NP451 aviation lubricating oil, may include:

[0103] S1, surface modification of inorganic filler.

[0104] The carbon fiber is dried, mixed with a silane coupling agent, added to deionized water, stirred and heated at 100°C, filtered, and dried in a vacuum drying oven at 100°C for 2 hours to obtain modified carbon fiber. The amount of the silane coupling agent added is 3% of the mass of the carbon fiber, and the average length of the carbon fiber is 3um.

[0105] S2, preparation of mixed emulsion.

[0106] Take 0.1g polytetrafluoroethylene emulsion, 0.1g perfluoroethylene propylene copolymer emulsion, and 0.6g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 12.5wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 12.5wt%, and the weight percentage of polyethersulfone emulsion is 75wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 100 nm.

[0107] S3, preparation of blended dispersion.

[0108] Take 0.3g of modified carbon fiber, 0.3g of mixed emulsion and 1.0g of alkylamine respectively and add them into the reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0109] S4, substrate pretreatment.

[0110] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0111] S5, preparation of composite coating.

[0112] The blended dispersion was coated on the clean surface of the workpiece and placed in a vacuum drying oven at 60°C for drying. After drying, it was placed in a muffle furnace and further sintered and cured at 300°C for 90 minutes to obtain a workpiece coated with a composite coating.

[0113] Embodiment 6:

[0114] A method for preparing a super-lubricating composite coating for aviation engine oil, oriented to NP451 aviation lubricating oil, may include:

[0115] S1, surface modification of inorganic filler.

[0116] The carbon fiber was dried, mixed with a silane coupling agent, added to deionized water, stirred and heated at 100°C, filtered, and dried in a vacuum oven at 100°C for 2 hours to obtain modified carbon fiber. The amount of silane coupling agent added was 3% of the mass of the carbon fiber, and the average length of the carbon fiber was 3 um.

[0117] S2, preparation of mixed emulsion.

[0118] Take 0.1g polytetrafluoroethylene emulsion, 0.1g perfluoroethylene propylene copolymer emulsion, and 0.6g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min, and finally a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 12.5wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 12.5wt%, and the weight percentage of polyethersulfone emulsion is 75wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 200nm.

[0119] S3, preparation of blended dispersion.

[0120] Take 0.3g of modified carbon fiber, 0.3g of mixed emulsion and 1.0g of polyacrylic acid respectively and add them into the reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0121] S4, substrate pretreatment.

[0122] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0123] S5, preparation of composite coating.

[0124] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven for drying at 60°C. After drying, it is placed in a muffle furnace and further sintered and cured at 290°C for 150 minutes to obtain a workpiece coated with a composite coating.

[0125] Embodiment 7:

[0126] A method for preparing a super-lubricating composite coating for aviation engine oil, oriented to NP451 aviation lubricating oil, may include:

[0127] S1, surface modification of inorganic filler.

[0128] The graphene was dried, mixed with dopamine, added into deionized water, stirred and heated at 100° C., filtered, and dried in a vacuum drying oven at 100° C. for 2 h to obtain modified graphene, wherein the amount of dopamine added was 3% of the mass of the graphene.

[0129] S2, preparation of mixed emulsion.

[0130] Take 0.2g polytetrafluoroethylene emulsion, 0.2g perfluoroethylene propylene copolymer emulsion, and 0.8g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 16.7wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 16.7wt%, and the weight percentage of polyethersulfone emulsion is 66.7wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 180 nm.

[0131] S3, preparation of blended dispersion.

[0132] Take 0.3g of modified graphene, 0.3g of mixed emulsion and 1.0g of deionized water respectively and add them into a reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0133] S4, substrate pretreatment.

[0134] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0135] S5, preparation of composite coating.

[0136] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven for drying at 60° C. After drying, it is placed in a muffle furnace and further sintered and cured at 280° C. The sintering and curing time is 200 minutes to obtain a workpiece coated with a composite coating.

[0137] Embodiment 8:

[0138] A method for preparing a super-lubricating composite coating for aviation engine oil, oriented to NP451 aviation lubricating oil, may include:

[0139] S1, surface modification of inorganic filler.

[0140] The graphene was dried, mixed with dopamine, added into deionized water, stirred and heated at 100° C., filtered, and dried in a vacuum drying oven at 100° C. for 2 h to obtain modified graphene, wherein the amount of dopamine added was 3% of the mass of the graphene.

[0141] S2, preparation of mixed emulsion.

[0142] Take 0.1g polytetrafluoroethylene emulsion, 0.1g perfluoroethylene propylene copolymer emulsion, and 0.6g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 12.5wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 12.5wt%, and the weight percentage of polyethersulfone emulsion is 75wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 250nm.

[0143] S3, preparation of blended dispersion.

[0144] Take 0.3g of modified graphene, 0.3g of mixed emulsion and 1.0g of deionized water respectively and add them into a reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0145] S4, substrate pretreatment.

[0146] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0147] S5, preparation of composite coating.

[0148] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven at 60°C for drying. After drying, it is placed in a muffle furnace and further sintered and cured at 350°C for 300 minutes to obtain a workpiece coated with a composite coating.

[0149] It should be noted that in other embodiments of the present application, if the inorganic particles use carbon fibers, the average length of the carbon fibers usually needs to meet 1 um~3 um, and if the inorganic particles use titanium dioxide nanoparticles, the average particle size of the titanium dioxide nanoparticles usually needs to meet 100 nm~200 nm. In practical applications, if the average length of the carbon fibers or the average particle size of the titanium dioxide nanoparticles is too large, the particles will settle, resulting in the inability to form a self-stratification phenomenon, and ultimately leading to the inability to reach a super-lubricating state; if the average length of the carbon fibers or the average particle size of the titanium dioxide nanoparticles is too small, the particle surface energy is large, and the curing process will result in poor surface bonding of the coating, poor bearing capacity, and ultimately the inability to maintain a stable friction coefficient. In other embodiments of the present application, the average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is maintained at 100 nm~300 nm, and the average particle size will affect the mixing effect.

[0150] In addition, when heating and curing, the temperature is 280-300 ° C, and the heating and curing is 100-150 min. The effect is better. Correspondingly, Example 1 and Example 3 are better embodiments of the present application. In practical applications, Example 1 has the best effect, and Example 3 has the second best effect. Other embodiments can also achieve superlubrication.

[0151] Comparative Example 1:

[0152] A method for preparing a super-lubricating composite coating for aviation engine oil, for NP451 aviation lubricating oil, wherein the super-lubricating composite coating cannot self-stratify, may include:

[0153] S1, surface modification of inorganic filler.

[0154] The graphene was dried, mixed with dopamine, added into deionized water, stirred and heated at 100° C., filtered, and dried in a vacuum drying oven at 100° C. for 2 h to obtain modified graphene, wherein the amount of dopamine added was 3% of the mass of the graphene.

[0155] S2, preparation of mixed emulsion.

[0156] Take 0.2g polytetrafluoroethylene emulsion and 0.6g polyethersulfone emulsion respectively, mix and add into the reagent bottle, shake it preliminarily, and then use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 30rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 25wt%, and the weight percentage of polyethersulfone emulsion is 75wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 150nm.

[0157] S3, preparation of blended dispersion.

[0158] Take 0.3g of modified graphene particles, 0.3g of mixed emulsion, and 1.0g of deionized water respectively, mix and add them into a reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm, and the ultrasonic time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0159] S4, substrate pretreatment.

[0160] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0161] S5, preparation of composite coating.

[0162] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven at 60°C for drying. After drying, it is placed in a muffle furnace and further sintered and cured at 280°C for 120 minutes to obtain a workpiece coated with a composite coating.

[0163] In order to verify the effect of the composite coating technology of comparative example 1, a friction test experiment was conducted. The workpiece coated with the composite coating was placed on a multifunctional friction and wear tester for friction testing, and 0.2g of NP451 aviation lubricant was added to the friction position, and a load of 5 N and a linear speed of 18 mm / s were applied at the same time. Figure 7 As shown, it is a SEM image of the cross section of the non-self-delaminating composite coating obtained in Comparative Example 1. Figure 6 The figure shows the friction test results of the composite coating obtained in Comparative Example 1. Figure 6 In the figure, the vertical axis Coefficient of Friction (COF) is used to describe the friction between two contacting surfaces. Figure 6 It can be seen that the friction coefficient of the composite coating obtained in Comparative Example 1 rises to 0.03, and a super-lubricating state cannot occur.

[0164] Comparative Example 2:

[0165] A method for preparing a super-lubricating composite coating for aviation engine oil, which is oriented to 5705 aviation lubricating oil, wherein the super-lubricating composite coating cannot self-stratify, and may include:

[0166] S1, surface modification of inorganic filler.

[0167] The titanium dioxide nanoparticles were dried, mixed with dopamine, added to deionized water, stirred and heated at 100°C, filtered, and dried in a vacuum drying oven at 100°C for 2 hours to obtain modified titanium dioxide nanoparticles. The amount of dopamine added was 3% of the mass of the titanium dioxide nanoparticles, and the average particle size of the titanium dioxide nanoparticles was 100 nm.

[0168] S2, preparation of blended dispersion.

[0169] Take 0.3g of modified titanium dioxide nanoparticles, 1.0g of polyethersulfone emulsion, and 1.0g of deionized water respectively, mix them and add them to a reagent bottle. After preliminary shaking, use an ultrasonic mixer to mix the mixed solution. The speed of the ultrasonic mixer is 20rpm, and the time is 10min. Finally, a uniformly dispersed blended dispersion is obtained.

[0170] S3, substrate pretreatment.

[0171] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0172] S4, preparation of composite coating.

[0173] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven at 60°C for drying. After drying, it is placed in a muffle furnace and further sintered and cured at 280°C for 120 minutes to obtain a workpiece coated with a composite coating.

[0174] In order to verify the effect of the composite coating technology of comparative example 2, a friction test experiment was conducted. The workpiece coated with the composite coating was placed on a multifunctional friction and wear tester for friction testing, and 0.2g of 5705 aviation lubricant was added to the friction position, and a load of 5 N and a linear speed of 18 mm / s were applied at the same time. Figure 8 The figure shows the friction test results of the composite coating obtained in Comparative Example 2. Figure 8 In the figure, the vertical axis Coefficient of Friction (COF) is used to describe the friction between two contacting surfaces. Figure 8 It can be seen that the friction coefficient of the composite coating obtained in Comparative Example 3 first increases and then stabilizes at 0.12.

[0175] Comparative Example 3

[0176] A method for preparing a super-lubricating composite coating for aviation engine oil, which is oriented to 5705 aviation lubricating oil, wherein the super-lubricating composite coating cannot self-stratify, and may include:

[0177] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0178] The cleaned workpiece after the above treatment was placed on a multifunctional friction and wear testing machine for friction testing. 0.2 g of 5750 aviation lubricant was added to the friction position, a load of 5 N was applied, and the friction test was carried out at a linear speed of 18 mm / s. Fig. 9 The figure is a schematic diagram of the friction test results of the composite coating obtained in Comparative Example 3. Fig. 9 It can be seen that the friction coefficient of the composite coating obtained in Comparative Example 3 gradually increases and the friction coefficient is as high as 0.4, and a super-lubricating state cannot occur.

[0179] Comparative Example 4:

[0180] A self-stratified super-lubricating composite coating for 5750 aviation lubricating oil and a method for achieving super-lubrication, the method comprising the following steps:

[0181] S1, surface modification of inorganic filler.

[0182] The titanium dioxide nanoparticles were dried, mixed with dopamine, added to deionized water, stirred and heated at 100°C, filtered, and dried in a vacuum drying oven at 100°C for 2 hours to obtain modified titanium dioxide nanoparticles. The amount of dopamine added was 3% of the mass of the titanium dioxide nanoparticles, and the average particle size of the titanium dioxide nanoparticles was 200 nm.

[0183] S2, preparation of mixed emulsion.

[0184] Take 0.35g polytetrafluoroethylene emulsion, 0.05g perfluoroethylene propylene copolymer emulsion, and 0.6g polyethersulfone emulsion respectively, add them to the reagent bottle, and use an ultrasonic mixer to mix the mixed solution after preliminary shaking. The speed of the ultrasonic mixer is 40rpm, and the ultrasonic time is 20min. Finally, a uniformly dispersed mixed emulsion is obtained. In the mixed emulsion, the weight percentage of polytetrafluoroethylene emulsion is 35wt%, the weight percentage of perfluoroethylene propylene copolymer emulsion is 5wt%, and the weight percentage of polyethersulfone emulsion is 60wt%. The average particle size of polytetrafluoroethylene emulsion and polyethersulfone emulsion is 150nm.

[0185] S3, preparation of blended dispersion.

[0186] Take 0.3g of modified titanium dioxide nanoparticles, 0.3g of mixed emulsion, and 1.0g of deionized water respectively, mix and add into the reagent bottle, shake preliminarily and mix the mixed solution with an ultrasonic mixer. The speed of the ultrasonic mixer is 20rpm and the ultrasonic time is 10min, finally obtaining a uniformly dispersed blended dispersion.

[0187] S4, substrate pretreatment.

[0188] The substrate was polished with 400# sandpaper to remove residual debris on the surface. The polished substrate surface was ultrasonically cleaned and then placed in an oven for drying to obtain a clean workpiece surface.

[0189] S5, preparation of composite coating.

[0190] The blended dispersion is coated on the clean surface of the workpiece and placed in a vacuum drying oven at 60°C for drying. After drying, it is placed in a muffle furnace and further sintered and cured at 280°C for 130 minutes to obtain a workpiece coated with a composite coating.

[0191] In order to verify the effect of the composite coating technology of comparative example 4, a friction test experiment was conducted. The workpiece coated with the composite coating was placed on a multifunctional friction and wear tester for friction testing, and 0.2g of 5750 lubricating oil was added to the friction position, while a load of 5 N and a linear speed of 18 mm / s were applied. Fig.10 Shown is a schematic diagram of the friction test results of the composite coating obtained in Comparative Example 4. Fig.10 In the figure, the vertical axis Coefficient of Friction (COF) is used to describe the friction between two contacting surfaces. Fig.10 It can be seen that the friction coefficient of the composite coating obtained in Comparative Example 4 maintained a short (30s) superlubricity state, and then rose to 0.18, and could not maintain a stable superlubricity state.

[0192] It can be seen from the above embodiments and comparative examples that the super-lubricating composite coating obtained by the method for preparing a super-lubricating composite coating for aviation engine oil of the present application can achieve a super-lubricating effect in the presence of aviation engine oil and has stable performance.

[0193] In addition, it should be noted that, in combination with the comparative examples of the present application, it can be seen that the ratio of the perfluoroethylene propylene copolymer emulsion, polytetrafluoroethylene emulsion, polyethersulfone emulsion, and modified inorganic particles in the present application has a significant effect on the superlubricity effect. In particular, the superlubricity composite coating of the present application can achieve a self-stratification effect. The specific principle is: the self-stratification phenomenon in the present application is mainly formed by the different polarities of different polymers (PTFE, FEP and PES). During the curing process of the blended dispersion, as the water continues to evaporate, the coated blended dispersion continues to solidify, the forces between the multiphase systems gradually become unbalanced, and the compatibility becomes worse and worse, and the trend of phase separation becomes greater and greater. Since the surface energy of FEP (Fluorinated ethylene propylene, fluorinated ethylene propylene copolymer) is quite different from the surface energy of PES (Polyethersulfone, polyethersulfone), the self-stratification from the phase separation causes FEP to move toward the air surface. When the proportion of FEP is small or FEP does not exist, the self-stratification phenomenon cannot be formed due to the small difference in surface energy between PTFE (Polytetrafluoroethylene, polytetrafluoroethylene) and PES.

[0194] In practical applications, when conducting friction test experiments, 5750 aviation engine oil or NP451 aviation engine oil can be evenly applied to the surface of the workpiece with the composite coating, and ceramic balls can be installed as a grinding pair to form a friction pair with the workpiece. The test machine is started to test the friction coefficient of the composite coating under aviation engine oil lubrication. Silicon nitride ceramic balls can be used as ceramic balls.

[0195] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a super lubricating composite coating for aviation engine oil, characterized in that: include: S1, using dopamine or silane coupling agent to perform surface modification treatment on carbon fiber, graphene or titanium dioxide nanoparticles to make the surface of carbon fiber, graphene or titanium dioxide nanoparticles wettable, washing and heat drying for 1-3 hours to obtain modified carbon fiber, graphene or titanium dioxide nanoparticles; S2, mixing a perfluoroethylene propylene copolymer emulsion, a polytetrafluoroethylene emulsion, and a polyethersulfone emulsion to obtain a mixed emulsion; S3, mixing the modified carbon fiber, graphene or titanium dioxide nanoparticles with the mixed emulsion, adding a solvent, and obtaining a blended dispersion; wherein the modified carbon fiber, graphene or titanium dioxide nanoparticles are 1 to 3 parts, the perfluoroethylene propylene copolymer emulsion is 10 to 20 parts, the polytetrafluoroethylene is 10 to 20 parts, and the polyether sulfone is 60 to 80 parts; S4, coating the blended dispersion on the surface of a workpiece lubricated with aviation engine oil, drying it, and then heating and curing it at a temperature of 280-380° C. for 100-300 min to obtain a composite coating.

2. A method for preparing a super lubricating composite coating for aviation engine oil according to claim 1, characterized in that: In step S1, when the carbon fiber is subjected to surface modification treatment, the average length of the carbon fiber is 1 um to 3 um.

3. A method for preparing a super lubricating composite coating for aviation engine oil according to claim 2, characterized in that: In step S1, when the titanium dioxide nanoparticles are subjected to surface modification treatment, the average particle size of the titanium dioxide nanoparticles is 100 nm to 200 nm.

4. A method for preparing a super lubricating composite coating for aviation engine oil according to claim 2 or 3, characterized in that: In step S2, the average particle size of the polytetrafluoroethylene emulsion and the polyethersulfone emulsion is 100 nm to 300 nm.

5. A method for preparing a super lubricating composite coating for aviation engine oil according to claim 4, characterized in that: In step S3, the solvent includes one or more of water, alkylamine, polyethyleneimine, polyacrylic acid, and polyethylene glycol.

6. A method for preparing a super lubricating composite coating for aviation engine oil according to claim 5, characterized in that: In step S4, the heating and curing comprises: Heat cure at 280-300°C for 100-150 min.

7. A super-lubricating composite coating for aviation engine oil, obtained by using the preparation method of the super-lubricating composite coating for aviation engine oil according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Lubricant composition containing ionic liquid and method for realizing super lubrication

    CN118028042A

  • Solid-liquid composite super-lubricating coating based on self-assembled monomolecular film and preparation method of solid-liquid composite super-lubricating coating

    CN118185459A

  • Preparation method of titanium dioxide nano powder-modified fluorine-containing acrylate emulsion

    CN103145912A

  • Graphene-modified composite solid lubricating coating, and preparation method and film forming technology thereof

    CN107603365A

  • Ceramic sol modified polyether-ether-ketone paint and preparation method thereof

    CN109054532A